Serum antioxidant micronutrient levels in pre-eclamptic pregnant women in Enugu, south-East Nigeria: a comparative cross-sectional analytical study - Joseph Tochukwu Enebe; Cyril Chukwudi Dim; Emmanuel Onyebuchi Ugwu; Nympha Onyinye Enebe; Ijeoma Angela Meka; Kingsley Chukwu Obioha; George Uchenna Eleje; Uchenna Ifeanyi Nwagha (BMC, 2020)
Abstract Background Pre-eclampsia is a common obstetric complication of pregnancy in Nigeria, and oxidative stress has been implicated in its aetiopathogenesis. Despite this fact, there is a paucity of information regarding the serum antioxidant micronutrient status of pre-eclamptic Nigerian women. The objective of the was to determine the mean serum levels of some antioxidant trace elements (copper, zinc, selenium, magnesium, manganese) in pre-eclamptic pregnant women and compare with that of healthy pregnant women in Enugu, South-Eastern, Nigeria. Methods A cross-sectional analytical study was carried out at the Obstetrics and Gynaecology department of the University of Nigeria, Teaching Hospital Ituku-Ozalla, Enugu. Using atomic absorption spectrophotometry, the sera of 81 pregnant pre-eclamptic and 81 matched healthy pregnant controls were analyzed for the antioxidant micronutrients. Both descriptive and inferential analysis was performed using the statistical package for social sciences (SPSS) version 21.0 and a P value of < 0.05 was considered to be statistically significant. Results The mean serum levels of copper, selenium, and magnesium were found to be significantly lower in the pre-eclamptic pregnant group when compared to the healthy pregnant controls (p < 0.05). The mean serum levels of zinc and manganese did not differ between the two groups (p > 0.05). All the mean serum levels of micro-nutrients studied did not vary by category of pre-eclampsia (with or without severity findings) except manganese which was significantly lower in pre-eclamptic women without severity findings when compared to those with severity findings (p = 0.043). Conclusions The serum levels of copper, selenium, and magnesium were significantly lower among pre-eclamptics when compared to their normal healthy controls. Low levels of selenium, copper, and magnesium may have contributed to the incidence of pre-eclampsia in our environment.